2021
DOI: 10.1016/j.ssmph.2021.100779
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early social support on subsequent health recovery after a major disaster: A longitudinal analysis

Abstract: Social support may facilitate disaster recovery. Prior analyses are hampered by the limits of cross-sectional approaches. We use longitudinal data from the KATIVA-NOLA survey to explore whether social support soon after Hurricane Katrina facilitated recovery of health status for a representative sample of 82 Vietnamese New Orleanians. Health and social support were assessed just before Hurricane Katrina (2005), soon afterwards (2006, 2007), and at longer durations post-disaster (2010, 2018). We use random effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
12
1
1
Order By: Relevance
“…This study's qualitative findings are relatively consistent with the results of a 14-year post-9/11 study of members of a registry of affected individuals, 44% of whom were injured, especially with fractures and dislocations, burns, and head injuries. 1 Long-term MH findings of the existing quantitative research on disaster survivors [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] resonate with this long-term study's qualitative findings. The 9/11 study 1 found that emotional distress and employment difficulties arising from the disaster generally improved across time; for some, however, these problems continued for long periods, changing people's lives forever.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…This study's qualitative findings are relatively consistent with the results of a 14-year post-9/11 study of members of a registry of affected individuals, 44% of whom were injured, especially with fractures and dislocations, burns, and head injuries. 1 Long-term MH findings of the existing quantitative research on disaster survivors [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] resonate with this long-term study's qualitative findings. The 9/11 study 1 found that emotional distress and employment difficulties arising from the disaster generally improved across time; for some, however, these problems continued for long periods, changing people's lives forever.…”
Section: Discussionmentioning
confidence: 67%
“…This study's qualitative findings are relatively consistent with the results of a 14-year post-9/11 study of members of a registry of affected individuals, 44% of whom were injured, especially with fractures and dislocations, burns, and head injuries. 1 Long-term MH findings of the existing quantitative research on disaster survivors [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] resonate with this long-term study's qualitative findings. A central strength of the current study is its prospective longitudinal, post-disaster follow-up, allowing survivors to describe their experiences and outcomes over a very long period of time spanning the time of the bombing to almost a quarter of a century later.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Future work should explore how and why social support fosters resilience; what features of social support are most critical; and whether the timing of social support matters. Bui, Anglewicz, and VanLandingham (2021), using a longitudinal research design, report that social support occurring soon after (within a year of) the Katrina disaster had positive implications for survivors' mental and physical health years later, even after controlling for Katrina-related damage and for pre-disaster social support and other characteristics (Bui, Anglewicz, and VanLandingham 2021). Additionally, when measuring social support, it is important to contextualize how social support is specifically manifested within different settings.…”
Section: Need More Attention and Emphasis On Social Supportmentioning
confidence: 99%